Utility of routine screening for alpha-1 antitrypsin deficiency in patients with bronchiectasis. Issue 7 (17th April 2020) - Carreto, Luis; Morrison, Meghan; Donovan, Jackie; Finch, Simon; Tan, Gan Liang; Fardon, Tom; Wilson, Robert; Furrie, Elisabeth; Loebinger, Michael; Chalmers, James D
Abstract : Alpha-1 antitrypsin deficiency (AATD) is a cause of bronchiectasis. Guidelines for bronchiectasis from the British Thoracic Society do not recommend to routinely test patients for AATD. In contrast, guidelines for AATD recommend routine screening. This contradiction, in part, results from the lack of data from large studies performing comprehensive screening. We screened 1600 patients with bronchiectasis at two centres in the UK from 2012 to 2016. In total, only eight individuals with AATD were identified representing 0.5% of the overall population. We conclude that routine screening for AATD in bronchiectasis in the UK has a low rate of detection. Further studies are required in different geographical regions, which may have a higher prevalence of AATD.